Efficacy of Bio-Insecticides and Synthetic Insecticides on the Control of Helicoverpa armigera Insect on Tomato Crop: Helicoverpa armigera Insect on Tomato Crop - Ahmad, Taimur; Khan, Rasool; Ullah, Mazhar; Khattak, Tariq Nawaz; Ahmad, Imtiaz; Khan, Ihsanullah; Khan, Ayaz; Khan, Saleem (Biological Sciences - PJSIR, 2020)
A field study was conducted to investigate the effect of botanical extracts i.e. neem oil emulsified with NIFA adjuvant, turmeric and hinge crude extracts and neem oil in combination with white oil emulsified with NIFA adjuvants and the synthetic insecticides i.e. emamectin and bifenthrin on the control of Helicoverpa armigera on tomato crop. It was found that the highest control of H. armigera was observed for emamactin and the lowest was recoded for control. Similarly, the highest yield of tomato was recoded for neem-white oil treatment and lowest infestation was recorded for emamactin benzoate. The neem oil and neem oil in combination with white oil emulsified with NIFA adjuvant also showedbetter results than bifenthrin and hinge and turmeric crude extracts in controlling the larvae population of H. armigera. On the basis of these findings, neem oil and neem oil combined with white oil is the best management technique for controlling the H. armigera, as these agents pose least environmental hazards and are relatively nontoxic to beneficial insects and humans and readily photodegrade. Keywords: